2021
DOI: 10.1093/ehjacc/zuab020.020
|View full text |Cite
|
Sign up to set email alerts
|

Sustained ventricular tachycardia in cardiogenic shock

Abstract: Funding Acknowledgements Type of funding sources: None. Introduction Cardiogenic shock (CS) and the presence of sustained ventricular tachycardia (VT) are indicators of worse prognosis in hospitalized patients. In patients severely ill, like patients with CS, the registration of VT can be a stressful situation as well a life threatening condition. Purpose Eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hence, the more frequent need for heart transplantation or VAD in the VA group without mortality difference suggest considering the occurrence of life-threatening VA as a pejorative turning point in heart failure, indicating a progression through the stages of disease severity. A retrospective monocentric study ( 14 ) directed on 222 patients (with 14 VT triggered CS) found similar results, emphasizing that even if VA can have a hemodynamic impact, it does not seem to increase early mortality. However, others reported that end-stage heart failure was the main cause of death after an electrical storm ( 20 ) which is consistent with our results considering all types of ventricular arrhythmia.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Hence, the more frequent need for heart transplantation or VAD in the VA group without mortality difference suggest considering the occurrence of life-threatening VA as a pejorative turning point in heart failure, indicating a progression through the stages of disease severity. A retrospective monocentric study ( 14 ) directed on 222 patients (with 14 VT triggered CS) found similar results, emphasizing that even if VA can have a hemodynamic impact, it does not seem to increase early mortality. However, others reported that end-stage heart failure was the main cause of death after an electrical storm ( 20 ) which is consistent with our results considering all types of ventricular arrhythmia.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, the relationship between VA and heart failure is still under debate ( 10 ). Even if mounting evidence indicates that high VA burden seems closely linked to mortality and outcomes in many settings of chronic heart failure ( 11 13 ), their significance in the context of CS remains unclear: whether the VA-triggered CS results in worse long-term outcomes than the non-VA-triggered one is not established ( 14 ).…”
Section: Introductionmentioning
confidence: 99%